Qualidade do sono em pacientes com síndrome do túnel do carpo - Pereira, Breno José Hülle [UNESP] (2016)
Frequently the symptoms of the carpal tunnel syndrome (CTS) occur at night time, but the relation between CTS and the sleep characteristics of those patients have yet to be systematically described by objective methods, such as conduction studies (ENMG) and polysomnography (PSG), which is the aim of this study. Methods: Consecutive female patients with CTS diagnosed by ENMG were studied by polysomnographic exams and listed in accordance with CTS severity, evaluated by distal motor latency of the median nerve of the affected hand or hands, and their polysomnographic data were analysed. Results: 42 patients were studied from June 2011 to June 2015. The Arousal Index (AI) of the patients with severe CTS were altered in larger proportion of those individuals than in those patients with slight or moderate CTS (100, 60% and 66%, respectively). This relation was also prevalent when the Desaturation Time (DT) was analyzed. Alterations of the Sleep Efficiency (SE) were more common among patients with bilateral CTS. Sleep architecture was equally altered among all patients, with slow wave sleep (SWS) and REM sleep diminished in all groups. The presence of Obstructive Sleep Apnea (OSA) was not dependent on CTS severity. Conclusions: The larger the CTS severity evaluated by ENMG, the more prevalent were fragmented sleep and sleep desaturation. Further analysis is required to ascertain causal relations between sleep quality and CTS severity.